Theory of planned behaviour analysis on entrepreneurial creativity - Pradana, Mahir; Kartawinata, Budi Rustandi; Syarifuddin, Syarifuddin; Wijaksana, Tri Indra; Utami, Fitriani Nur; Putra, Adrianza (Creativity Studies, 2024)
The importance of entrepreneurial education in Indonesian higher education has been argued. In this study, we examined how entrepreneurial creativity, a crucial aspect of entrepreneurship education, contributes significantly to the emergence of entrepreneurial qualities. The theory of planned behaviour serves as the theoretical underpinning for the questionnaire we developed for this quantitative investigation. For this study, we polled 400 college students from numerous private colleges in Indonesia. We ran a route analysis on the data using SmartPLS version 3 as our analysis tool. Our findings demonstrate that when theory of planned behaviour variables have an impact on creativity, which means that subjective norm, attitude toward entrepreneurship, and perceived behavioural control should be focused on because these factors eventually have crucial impact on entrepreneurial creativity.